Nurse workload at the hospital level: a bibliographic review - Abanto Zaña, Anghela Zuleyka (2024)
Since ancient times, the nursing professional has been developing multiple functions in order to satisfy the needs of users and preserve their safety. However, these functions contribute to the work overload of nursing staff; which is being prioritized and attended to since its outcome is closely related to the quality of care and the health of the professional who offers care. Objective: Identify the determinants of nursing workload and describe the consequences suffered by nurses at the hospital level through a systematic review. Method: a systematic review of articles published in the period 2015 to 2023 was carried out in the various databases. For the search strategy, the acronym PCC and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart were used. Main results: 1,729 articles were obtained and after applying the inclusion and exclusion criteria, 46 articles were selected, of which only 20 were useful for the review, resulting in hospital admission and clinical complexity being the determinants of the burden. work of the nursing professional at the hospital level. General conclusion: The workload of the nursing professional is determined by the hospital admission and the complexity of patient care; having consequences on nursing care (poor satisfaction of the patient's needs and low quality of care provided) and on the life of the nursing professional due to the deterioration of physical and mental health.